The Tritryps Comparative Repeatome: Insights on Repetitive Element Evolution in Trypanosomatid Pathogens. (4th February 2019) - Pita, Sebastián; Díaz-Viraqué, Florencia; Iraola, Gregorio; Robello, Carlos
Abstract: The major human pathogens Trypanosoma cruzi, Trypanosoma brucei, and Leishmania major are collectively known as the Tritryps. The initial comparative analysis of their genomes has uncovered that Tritryps share a great number of genes, but repetitive DNA seems to be extremely variable between them. However, the in-depth characterization of repetitive DNA in these pathogens has been in part neglected, mainly due to the well-known technical challenges of studying repetitive sequences from de novo assemblies using short reads. Here, we compared the repetitive DNA repertories between the Tritryps genomes using genome-wide, low-coverage Illumina sequencing coupled to RepeatExplorer analysis. Our work demonstrates that this extensively implemented approach for studying higher eukaryote repeatomes is also useful for protozoan parasites like trypanosomatids, as we recovered previously observed differences in the presence and amount of repetitive DNA families. Additionally, our estimations of repetitive DNA abundance were comparable to those obtained from enhanced-quality assemblies using longer reads. Importantly, our methodology allowed us to describe a previously undescribed transposable element in Leishmania major (TATE element), highlighting its potential to accurately recover distinctive features from poorly characterized repeatomes. Together, our results support the application of this low-cost, low-coverage sequencing approach for the extensive characterization of repetitive DNA evolutionary dynamics in trypanosomatid and other protozoan genomes.